1997
DOI: 10.1021/jo971081t
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Alkylation of π-Rich, Acid-Sensitive Heterocyclic Compounds via Essentially Free Carbocations1

Abstract: Alkylation of pi-rich heteroaromatics such as pyrroles and furans by the standard Friedel-Crafts approach is impractical because the acid catalysts employed (Brønsted or Lewis) induce polyalkylation, ring opening, and polymerization. The present study describes the facile benzylation of pi-excessive heteroaromatics using the nitrosoamide approach, which generates nitrogen-separated carbocation-counterion ion-pairs as the alkylating agent with no catalyst being required. N-Nitrosoamides are favorable sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The partitioning of the benzyl carbocation, generated from the decomposition of N -benzyl- N -nitrosobenzamide or the protonation of phenyldiazomethane by benzoic acid, between nucleophilic addition of solvent and trapping by benzoate ion within an ion pair results in a higher yield of the solvent adduct in a solvent of pyrrole than in a solvent of methanol . This observation is in qualitative agreement with the results reported here that pyrrole is more reactive than the hydroxylic solvent water toward 1 + .…”
Section: Discussionsupporting
confidence: 90%
“…The partitioning of the benzyl carbocation, generated from the decomposition of N -benzyl- N -nitrosobenzamide or the protonation of phenyldiazomethane by benzoic acid, between nucleophilic addition of solvent and trapping by benzoate ion within an ion pair results in a higher yield of the solvent adduct in a solvent of pyrrole than in a solvent of methanol . This observation is in qualitative agreement with the results reported here that pyrrole is more reactive than the hydroxylic solvent water toward 1 + .…”
Section: Discussionsupporting
confidence: 90%
“…Benzylamine was used as nucleophile and 1b instead of 1a was used as substrate. Both 1 H NMR and 13 C NMR spectra of the product correspond to literature spectra of N-benzylbenzamide, [32][33][34] corroborating the view that nucleophilic substitution did indeed take place. Reaction between 1b and phenylamine in benzene was shown to yield N-phenylbenzamide.…”
Section: 31supporting
confidence: 76%
“…We earlier reported that carbocations formed from alkyldiazonium carboxylate ion pairs are highly reactive species that have the capability of alkylating most organic molecules of which a solvent cage could be comprised (eq 1).
…”
mentioning
confidence: 99%